The inhibitory effect of lemon juice (citrus limon) on vibrio parahaemolyticus in raw oyster (crassostrea virginica) / Siti Farah Alwani Mohd Nawi … [et al.] - Mohd Nawi, Farah Alwani; Mohd Zain, Zaini; Zahari, Muhammad Zarif; Abdul Hamid, Anis Amalina; Ahmad Afandi, Nur Fakhriah; Haris Fadzilah, Nur Zahirah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Serving raw oysters with lemon juice is a delicacy in many restaurants in Malaysia. Oysters (Crassostrea virginica) live in the seacoast and they share the same environment as Vibrio parahaemolyticus. Consumption of raw oysters contaminated with V. parahaemolyticus can lead to severe gastroenteritis. A study was performed to determine whether lemon (Citrus limon) juice is able to inhibit the growth of V. parahaemolyticus after being inoculated in raw oysters. Methods: Frozen oysters bought from a local supplier weighing 6 g each were minced and placed in two bottles using sterile technique. Approximately 1 ml of 107 CFU of V. parahaemolyticus (ATCC strain 17802) was added and mixed in both bottles. The mixture was treated with 1 ml of lemon juice in only one of the bottles and the other bottle served as a control. At every 30 s intervals for 2 min, 1 g of the sample was taken for enumeration of viable cells onto thiosulphate citrate bile salt sucrose (TCBS). Results: After 30 s of treatment with the lemon juice, it was observed that the number of colonies in the treated samples reduced from 7 Log to 3 Log. Subsequently, no viable V. parahaemolyticus was seen. It was also observed that there were 3 Log reductions of V. parahaemolyticus after 30 s in untreated samples, however the number of colonies remained stable until the end of the experiment. Conclusion: This study therefore shows that lemon juice has some antimicrobial effect on V. parahaemolyticus in raw oysters.